Improving relations between users and libraries: a survey of Chinese academic libraries. Issue 4 (1st August 2016) - Zhai, Xiaojuan; Wang, Jingjing
Abstract : Purpose: This study aims to investigate the effectiveness of library services according to user experiences (UXs). The study discusses underlying internal problems existing in libraries that affect user satisfaction. Furthermore, it seeks to identify ways to improve the UX. Design/methodology/approach: The methodology comprised a questionnaire administered at Nanjing University Library, China. The survey examined users' satisfaction with the online public access catalogue, locating books on the shelves, and users' participation in the organization of library resources. This study used the annual reading quantity of users system, a new system of measurement that distinguishes between informal and avid library users. Findings: The data analysis indicated poor user satisfaction. The problems were mainly associated with the libraries' resource organization, such as descriptive cataloguing, subject headings and classification, which is controlled by library administration. Moreover, users' feedback is not integrated within the library system. Because of the process-oriented architecture of the current integrated library system, librarians and users do not communicate effectively. These barriers between users and the library staff members are difficult to overcome. Originality/value: The study describes that the results relate to user satisfaction with searching and locating books based on the patron's reading level. Differences were observed between light and avid readers in terms of satisfaction with the ease of searching and finding books. This demonstrates the internal connections of these results with library procedures. Furthermore, this study identifies improvement measures to resolve these problems.